The bacteriology of the small intestinal mucosa of free-living reindeer - Sørmo, Wenche; Aagnes, Tove H.; Olsen, Monica A.; Mathiesen, Svein D. (Rangifer, 1994)
Bacteria in close associaton with the intestinal mucosa are thought to protect the mucosa from pathogenic microorganisms. The pH of the small intestinal mucosa and the viable populations of aerobic and anaerobic bacteria associated with the proximal and distal jejunal mucosa, were measured in four free-living reindeer in winter. The anaerobic bacterial populations were characterized. The median pH of the mucosa of the duodenum was 6.6 (n=4) at point 0.2 m from the pyloric sphincter. The mucosal pH increased along the length of the intestine to 8.3 at 14 m and then decreased to 7.9 at 19.8 m from the pyloric sphincter. Examination by transmission electron microscopy and cultivation techniques failed to reveal any bacteria on the mucosa of the proximal jejunum in two of the animals. In two other reindeer the median anaerobic bacterial densities in the proximal jejunum ranged from 25-2500 cells/g mucosa. The median anaerobic bacterial populations in the distal jejunum ranged from 80 to 20000 bacteria/g mucosa (n=4). The anaerobic population of bacteria in the proximal jejunum was dominated by streptococci and unidentified gram positive rods. Bacteroidaceae, streptococci and unidentified gram positive rods were common in the distal jejunum. The low density and the species diversity of bacteria in the small intestine suggests that these microorganisms are inhibited by components in the natural winter diet of reindeer. Bacteria evidently play a minor role in protection of the mucosa of reindeer in winter.